Placenta percreta management in a rural setting: a case report - Shrestha, Shailesh Prasad; Bhandari, Bibek (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Placenta accreta spectrum, formerly known as morbidly adherent placenta, refers to the range of pathologic adherence of the placenta. Placenta accreta spectrum is a complicated pregnancy linked to significant maternal and fetal health risks. There should be high suspicion for placenta accreta spectrum in previous cesarean delivery to early diagnose and treat the condition. Placenta accreta spectrum can be classified into three groups: placenta accreta, where the villi attach to the myometrium; placenta increta, where the villi invade the myometrium; and placenta percreta, where the villi penetrate the entire thickness of the myometrium. We report a case of placenta percreta who underwent cesarean hysterectomy while working in a resource-limited setting of rural Nepal.